Lay persons alerted by mobile application system initiate earlier cardio-pulmonary resuscitation: A comparison with SMS-based system notification. (May 2017) - Caputo, Maria Luce; Muschietti, Sandro; Burkart, Roman; Benvenuti, Claudio; Conte, Giulio; Regoli, François; Mauri, Romano; Klersy, Catherine; Moccetti, Tiziano; Auricchio, Angelo
Abstract: Aim: We compared the time to initiation of cardiopulmonary resuscitation (CPR) by lay responders and/or first responders alerted either via Short Message Service (SMS) or by using a mobile application-based alert system (APP). Methods: The Ticino Registry of Cardiac Arrest collects all data about out-of-hospital cardiac arrests (OHCAs) occurring in the Canton of Ticino. At the time of a bystander's call, the EMS dispatcher sends one ambulance and alerts the first-responders network made up of police officers or fire brigade equipped with an automatic external defibrillator, the so called "traditional" first responders, and – if the scene was considered safe – lay responders as well. We evaluated the time from call to arrival of traditional first responders and/or lay responders when alerted either via SMS or the new developed mobile APP. Results: Over the study period 593 OHCAs have occurred. Notification to the first responders network was sent via SMS in 198 cases and via mobile APP in 134 cases. Median time to first responder/lay responder arrival on scene was significantly reduced by the APP-based system (3.5 [2.8–5.2]) compared to the SMS-based system (5.6 [4.2–8.5] min, p 0.0001). The proportion of lay responders arriving first on the scene significantly increased (70% vs. 15%, p < 0.01) with the APP. Earlier arrival of a first responder or of a lay responder determined a higher survival rate. Conclusions: The mobile APP system is highly efficient in the recruitment of first responders, significantly reducing the time to the initiation of CPR thus increasing survival rates.